An Insight Into Buccal Drug Delivery System - Alagarsamy, Shanmugarathinam; Vasam, Mallikarjun; Ravindran, Saravanan (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2019)
Oral drug delivery still remains the first choice as it offers wider range of advantages comparing to other route of administrations. Drug delivery systems are continuously advancing in the pharmaceutical discipline. The anatomy and physiological characteristics of oral cavity attracted the formulation scientist to work on newer buccal based system. Oral mucosal drug delivery system offers certain advantages; by passes first pass metabolism, rapid absorption, quick on set action. Barriers available in the oral epithelium shall be modified using the permeation enhancers using various approaches. Buccal drug delivery system has various formulation strategies including solid, semi-solid and liquid dosage forms. Oral buccal mucoadhesive system has well established in vitro, ex vivo and in vivo evaluations parameters. This review outlines the various concepts in buccal drug delivery system.